2021
DOI: 10.1371/journal.pone.0247700
|View full text |Cite
|
Sign up to set email alerts
|

Assessing service availability and readiness to manage Chronic Respiratory Diseases (CRDs) in Bangladesh

Abstract: Introduction Chronic Respiratory Diseases (CRDs) are some of the most prevailing non-communicable diseases (NCDs) worldwide and cause three times higher morbidity and mortality in low- and middle-income countries (LMIC) than in developed nations. In Bangladesh, there is a dearth of data about the quality of CRD management in health facilities. This study aims to describe CRD service availability and readiness at all tiers of health facilities using the World Health Organization’s (WHO) Service Availability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 16 publications
5
14
0
Order By: Relevance
“…The explanatory variables were chosen based on two criteria: (1) they were available in the SPA survey [29][30][31] and (2) previous research had established them as important determinants of readiness of health facilities to provide DM services. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] The following variables were considered: facility location, managing authority, facility type, external sources of revenue, quality assurance activities, routine management meetings, external supervision, user fees, presence of trained health provider at facility 24 hours with duty schedule or present on-call, feedback on clients' opinions, health facility's' ability to perform diagnosis and/or treatment, and number of trained DM care providers.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…The explanatory variables were chosen based on two criteria: (1) they were available in the SPA survey [29][30][31] and (2) previous research had established them as important determinants of readiness of health facilities to provide DM services. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] The following variables were considered: facility location, managing authority, facility type, external sources of revenue, quality assurance activities, routine management meetings, external supervision, user fees, presence of trained health provider at facility 24 hours with duty schedule or present on-call, feedback on clients' opinions, health facility's' ability to perform diagnosis and/or treatment, and number of trained DM care providers.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…With reference from previous studies assessing health facilities' readiness in services delivery, 70% GSR score was considered to be the cut-off point, where facilities that scored 70% or higher were considered to be ready to offer the expected health services. [31,32,42,43] In this study, the GSR index of 87%, is above the threshold, implying that the health facilities in the study area are generally ready for health services delivery. A report from the Ministry of Health [24] on service availability and readiness assessment conducted in 27 districts of Tanzania found that the private facilities including faith-based ones, had higher scores on the GSR index than the government facilities.…”
Section: Health Facilities' General Service Readiness For Health Serv...mentioning
confidence: 57%
“…The overall mean GSR score of all SDPs was 83.4%. Facilities with a general readiness score of 70% are generally considered as having good service readiness [ 29 , 30 ]. Comparing this to the average GSR score in this study the present results show that SDPs in Ghana generally have good service readiness.…”
Section: Discussionmentioning
confidence: 99%